Rapid production of biodiesel in a microchannel reactor at room temperature by enhancement of mixing behaviour in methanol phase using volume of fluid model - Mohd Laziz, A. (Elsevier Ltd, 2020)
The demand for biodiesel to reduce consumption of fossil fuels has motivated engineers to design a rapid and safe production process. However, the slow mass transfer of multiphase transesterification reaction hinders the overall reaction time. A continuous process using a microchannel reactor was proven to achieve complete reaction time in 40 s with high oil conversion of 98.6 due to the enhancement of mixing inside the methanol slug phase. The reaction was successfully performed at ambient room environment, without heating element in the reactor that reduces the design complexity and makes the operation energy efficient and safer. The enhancement of reaction was investigated based on the hydrodynamic factors such as interfacial area and mixing. Three-dimensional Computational Fluid Dynamics (CFD) simulation shows a torus-shaped recirculation structure inside methanol slug that enhances mixing. Microchannel reactor has been proven to enhance the mixing and capable in having faster, highly efficient, and safer process. Â© 2020 Elsevier Ltd